2003
DOI: 10.1073/pnas.1936193100
|View full text |Cite
|
Sign up to set email alerts
|

HeT-A elements in Drosophila virilis : Retrotransposon telomeres are conserved across the Drosophila genus

Abstract: Drosophila melanogaster telomeres are composed of two retrotransposons, HeT-A and TART. Drosophila virilis has recently been shown to have telomere-specific TART elements with many of the characteristics of their D. melanogaster homologues. We now report identification of the second telomere-specific retrotransposon, HeT-A, from D. virilis. These results show that HeT-A and TART have been maintaining telomeres in Drosophila for more than the 60 million years that separate D. melanogaster and D. virilis. All Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…2), where a TART-like element (a TR) and a HeT-A-like element (a HTR) had been previously identified. 58,59 The comparison between all Drosophila telomeric retrotransposons clearly shows an extensive evolution of these elements over a 60 million years time frame. Thus, it is normal to find deletions of varied sizes in different upstream regions with respect to the zinc knuckles domain of the ORF1.…”
Section: Rapid Evolution Of Drosophila Telomeric Retrotransposonsmentioning
confidence: 99%
“…2), where a TART-like element (a TR) and a HeT-A-like element (a HTR) had been previously identified. 58,59 The comparison between all Drosophila telomeric retrotransposons clearly shows an extensive evolution of these elements over a 60 million years time frame. Thus, it is normal to find deletions of varied sizes in different upstream regions with respect to the zinc knuckles domain of the ORF1.…”
Section: Rapid Evolution Of Drosophila Telomeric Retrotransposonsmentioning
confidence: 99%
“…Nonetheless, HeT-A and TART arrays maintain the strand composition bias seen on other telomeres-the sense strand is always A+C-rich (Danilevskaya et al 1998), like telomerase template sequences (Henderson 1995). In addition, HeT-A 3Ј UTRs have a pattern of irregularly spaced A-rich regions in every Drosophila species studied (Danilevskaya et al 1998;Casacuberta and Pardue 2003).…”
mentioning
confidence: 99%
“…A HeT-A element was found in the terminal array next to a TART from D. virilis. As with its homolog in D. melanogaster, the HeT-A element carried only a single ORF for a Gag protein and had a long 3' UTR (Casacuberta & Pardue, 2003b). Experiments to localize GFP-tagged Gag proteins indicated that the Gag encoded by the D. virilis TART element requires HeT-A Gag to target the telomeres, similar to the situation found in D. melanogaster (Casacuberta et al, 2007).…”
Section: Drosophila Virilismentioning
confidence: 60%